The Influence of Leadership on Employee Performance At the Education and Culture Office, West Seram Regency - Akrim Hehanusa; Petronela Sahetapy; Josep A Ufie (Journal of Government Science Studies, 2026)
This study aims to analyze the influence of leadership style on employee performance at the Department of Education and Culture of West Seram Regency, and to describe and analyze the significance of the relationship between leadership style and employee performance at the same institution. The research design is a logical plan for testing the hypotheses. This study is descriptive in nature and employs a survey method. The population consists of 47 individuals, and the sample was taken using a census technique. The data were analyzed using frequency tables, frequency distribution, summarization and interpretation, descriptive analysis, and the Product-Moment correlation formula. The results show that the leadership style implemented by the head of the Department of Education and Culture of West Seram Regency falls into the “good” category, with a 87.27 percent level. Employee performance at the same institution is categorized as high, with an 84.89% level. In addition, the study found a relationship between leadership style and employee performance at the Department of Education and Culture of West Seram Regency, as the calculated r-value (0.918) exceeds the table r-value (0.288). Therefore, it is concluded that leadership style influences employee performance at the Department of Education and Culture of West Seram Regency, with a very high level of influence.